PERENCANAAN TATA KELOLA ASET IT YANG DIKELOLA OLEH PRODI PTI DI STKIP TAMAN SISWA BIMA MENGGUNAKAN COBIT 2019 - Muhammad Imam Munandar; Alva Hendi Muhammad; Asro Nasiri (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Abstract: PTI Study Program (Information Technology Education) STKIP Taman Siswa Bima which really needs supporting facilities in terms of learning and improving students' abilities in the learning process. The availability of IT asset services can support and progress the STKIP Taman Siswa Bima Institute in the process of increasing accreditation in terms of institutional facilities. Investment in the procurement of IT Assets Requires a lot of money to support the continuity of pre-learning, therefore the process of purchasing, maintaining and maintaining IT assets will make it easier for parties to procure IT Assets. This will have an impact on reporting on organizational goals. This study uses the COBIT 2019 framework. The results of this study determine the current capability level conditions in the PTI STKIP Taman Siswa Bima Study Program, namely the average activity in the BAI09 subdomain is at the level that is carried out by the process. The target capability level which I hope to be at level 3 for the next year. Recommendations for improvements are made in stages according to the 2019 COBIT reference.